Envy : a luxe novel - Godbersen, Anna. (New York : Harpercollins, 2009)
Manhattan's most envied residents appear of have everything they desire: wealth, beauty, happiness. But sometimes the most practiced smiles hide the most scandalous secrets.
Keywords: Sisters -- Juvenile fiction; Conduct of life -- Juvenile fiction; Social classes -- Juvenile fiction; Rich people -- Juvenile fiction; Upper class -- New York (State) -- New York -- Juvenile fiction; New York (N.Y.) -- Social life and customs -- 19th century -- Juvenile fiction